O Programa Mais Alfabetização na visão de professoras alfabetizadoras de uma escola da Rede Municipal de ensino de Corumbá-MS - Eliane Damasceno da Silva (2021)
This dissertation is part of the research line “Educational practices, training of teachers/educators in school and non-school spaces” of the Master’s in Education course of the Graduate Program in Education of the Pantanal Campus, Mato Grosso do Sul Federal University, Concentration area in Social Education. It assumes that the appropriation of reading and writing is essential in contemporary society and influences people's daily lives, being necessary to ensure the child's literacy process and the training of teachers who work in the Early Years of Elementary School. It has as its problem the discontinuity in literacy teachers’ training policies. To this end, the More Literacy Program was taken as the object of study as it was developed in the city of Corumbá between 2018 and 2019, seeking to answer the following central question: what is the impact of the More Literacy Program on the participant teachers’ view? Thus, in this study, we tried to give a voice to teachers when we tried to answer the following questions: how was the More Literacy Program developed in the municipal public education system of Corumbá? How many schools were covered? What is the involved teachers’ evaluation in relation to the development of the program at the school? To answer these questions, the present research had as general objective to understand the literacy teachers’ vision about the impact of More Literacy Program on their training and literacy practices at a municipal public education system school of Corumbá-MS. The specific objectives sought to: a) Raise the history of More Literacy Program from the national scene to the local (Corumbá). b) Map the number of schools and teachers, teachers and assistant teachers who joined and worked in the More Literacy Program in 2018 and 2019 in the municipal public education system of Corumbá-MS. c) Reflect the teachers' vision regarding the program daily development, as well as its effects on one of the schools served. With a qualitative approach regarding the nature of the study and exploratory and descriptive in relation to the objectives, it is also configured as a case study, with the triangulation of the following sources and instruments: (i) guiding documents of the More Literacy Program for analysis of the Pedagogical Guidance and Monitoring System Operational Manual and the Ordinance establishing the More Literacy Program; (ii) data from the Municipal Education Secretary of Corumbá through a questionnaire answered by the responsible technician for the program; and (iii) testimonies of five literacy teachers based on interviews. The analyzes focused on the daily development and on the effects of the program, indicating as impacts: the absence of continuing education, lack of methodological structure and time to develop systematized and collaborative work. Another aspect refers to the restricted view of literacy presented in the document, which highlights the need for pedagogical knowledge inherent to literacy. Therefore, it is concluded that actions such as the analyzed program in this study need to focus on the training of teachers based on the reflection of the demands present in everyday school life.